Comparative analysis of Defensible Space in CPTED housing and non-CPTED housing. Issue 4 (December 2015) - Ha, Taehoon; Oh, Gyeong-Seok; Park, Hyeon-Ho
Abstract: Pangyo New Town located in Greater Seoul, South Korea was the first new town development in which CPTED has been applied from the planning stage, and they created their own "Crime Prevention Design Guideline" by modifying the existing regulations of the successful cases of UK, US, and Canada developing them to match South Korean culture. However, there is no clear support of the effectiveness and benefits of CPTED in Korea so far, based on the available data. This research could be a good start in finding out its benefits and effects. In order to pursue this research, two different new towns were selected. Both towns have similar populations and characters, one that has adopted CPTED and the other that has not. Then, crime rates for these selected towns were collected and compared to find out whether there is any evidence that adopting CPTED has positive effects in reducing crime incidents. In addition, qualitative analysis of the new towns was performed with the "CPTED Audit Checklist" and the "CPTED Post-Audit Evaluation Worksheet" to learn how CPTED principles were applied and implemented in the new town development.